From the Guest Editors - Alberto d’Onofrio; Paola Cerrai; Alberto Gandolfi (Mathematical Biosciences and Engineering)
There is an increasing awareness that to properly understand how tumorsoriginate and grow, and then how to develop effective cures, it must be taken into accountthe dynamics of tumors and its great complexity. Tumors are characterized not only by thecoexistenceof multiple scales, both temporal and spatial, but also by multiple and quitedifferent kinds of interactions, from chemical to mechanical. This makes thestudyof tumors remarkably complicated. A genuine explosion of data concerning themulti-faceted aspects of this family of phenomena collectively called cancers,is now becoming available. At the same time, it is becoming quite evident thattraditional tools from biostatistics and bioinformatics cannot manage thesedata. Mathematics, theoretical biophysics and computer sciences are needed toqualitatively andquantitatively interpret experimental and clinical results, in order to makerealistic predictions.For more information please click the “Full Text” above.